Are head-down tilt bedrest studies capturing the true nature of spaceflight-induced cognitive changes? A review - Barkaszi, Irén; Ehmann, Bea; Tölgyesi, Borbála; Balázs, László; Altbäcker, Anna (Frontiers in Physiology, 2022)
Although numerous studies have examined cognitive functions in space, the reasons behind the observed changes described by space research and anecdotal reports have not yet been elucidated. One potential source of cognitive changes is the cephalad fluid shift in the body caused by the lack of hydrostatic pressure under microgravity. These alterations can be modeled under terrestrial conditions using ground-based studies, such as head-down tilt bed rest (HDBR). In this review, we compare the results of the space and HDBR cognitive research. Results for baseline and in-flight/ in-HDBR comparisons, and for baseline and post-flight/post-HDBR comparisons are detailed regarding sensorimotor skills, attention, psychomotor speed, memory, executive functions, reasoning, and mathematical processing. Beyond behavioral performance, results regarding brain electrical activity during simulated and real microgravity environments are also discussed. Finally, we highlight the research gaps and suggest future directions.